Effects of antibiotics on the anaerobic digestion process - Hawley, W.N.J. (2017)
The key product from anaerobic digestion (AD) is biogas, which is used to generate heat and/or electricity. Anaerobic digestion involves degradation and stabilisation of the feedstock by microorganisms, leading to the formation of biogas and a digestate residue, which is used as a fertiliser. Contaminants entering the system in the feedstock may limit biogas yield if functioning of the methanogenic archaea is disrupted. Digestate quality may also be compromised. Approximately 40% of the current UK biogas plants are farm-based, using manures and slurry as the main feedstock. Veterinary medicines are excreted in dung of treated animals and if used prophylactically, concentrations in the faeces or urine may be significant. Contaminated animal waste is therefore likely to be used as a feedstock in AD. Since digestates are commonly used as fertilisers, contaminant loading and fate must be understood to prevent transfer into crops, reductions in soil microbial activity, increased antibiotic resistance and detrimental effects to livestock if digestates are applied to fodder crops or pasture. It is unlikely that the use of veterinary pharmaceuticals will be reduced whilst livestock farming is intensifying and the current demand for meat is growing, therefore understanding the operational processes of AD that influence the persistence of commonly used veterinary medicines and subsequent toxicity are crucial to minimising potentially detrimental effects. Research was undertaken using laboratory-scale digestion vessels to quantify the effect of the commonly used veterinary antibiotics, oxytetracycline and tylosin, when added to naïve (organic) cattle dung or to slurry from a conventional dairy farm. Anaerobic digestion units were spiked with either oxytetracycline or tylosin at low (environmentally realistic) and artificially high concentrations, either at start-up (day 0) or once the system was producing gas (day 15). Biogas production was measured and gas collected every 5 days to quantify the temporal effect of the antibiotics on methane production. Oxytetracycline and tylosin significantly reduced both biogas quality and quantity, with the extent of the effect differing with each feedstock. In organic cow dung, the low (4.33 mg L-1) and artificially high (86.63 mg L-1) concentration of oxytetracycline added on day 15 to organic cow dung caused an overall drop in biogas production of 12% and 25% respectively, whilst the same concentrations incorporated at start-up caused a drop of only 4% and 18% respectively. Both the low and artificially high concentrations of tylosin added on day 15 caused a 33% drop in biogas production, whilst the same concentrations incorporated on day 0 caused a drop of 15% and 42% respectively. In conventional dairy slurry, low (4.33 mg L-1) and artificially high (86.63 mg L-1) concentrations of oxytetracycline caused an overall 3% and 10% drop in biogas production respectively, with tylosin amendment causing a decrease in total biogas production of 7% and 22% respectively. Feedstock origin affected biogas production and quality when the system was challenged by antibiotic inputs. These data highlight the complex interactions that can occur between feedstock and exposure to veterinary pharmaceuticals.